Case report: The treatment for olfactory neuroblastoma combined with leptomeningeal carcinomatosis via an ommaya reservoir - Peng, Yichen; Kang, Xun; Jiang, Bo; Chen, Feng; Yang, Shoubo; Kang, Zhuang; Wang, Ce; Lin, Yi; Li, Shenglan; Han, Jiefei; Zhang, Botao; Zhang, Weichunbai; et al. (Frontiers in Oncology, 2023)
Olfactory neuroblastoma is a rare neoplasm that usually presents in the upper nasal cavity. Although its prognosis is highly unfavorable, effective treatment options are still lacking. Moreover, there is no standard treatment for patients with olfactory neuroblastoma that progressed to leptomeningeal carcinomatosis. Here we report an uncommon case of a 59-year-old woman who was diagnosed with olfactory neuroblastoma and leptomeningeal carcinomatosis. For a direct delivery of the drugs to the tumor, and to avoid the impact of lumbar puncture on the patient's quality of life, the intravenous chemotherapy plus intrathecal administration of MTX via an Ommaya reservoir was chosen. The results were striking, with the disappearance of tumor cells in the cerebrospinal fluid and the relief of the patient's symptoms with PR. Our result indicates that chemotherapy via an Ommaya reservoir offers a new potential therapy for patients with meningeal metastases.